Complications in Non-Vascular Interventional Therapy and Interventional Oncology - Mueller-Huelsbeck, Stefan (Thieme Medical Publishers, Incorporated, 2019)
Learn to avoid and manage complications from non-vascular interventional and interventional oncological procedures The range of non-vascular procedures that can be performed in interventional imaging is vast and includes management of a wide range of conditions, such as treatment of kidney stones, obtaining diagnostic biopsies in suspected cancers, bile duct occlusions, compression fractures, drainage of abscesses, collection of fluids, etc. In particular, various cancers often lend themselves well to local tumor destruction with interventional techniques, while holding morbidity and mortality.